2009
DOI: 10.1104/pp.109.148908
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Casein Kinase II in Flowering Time Regulation Has Diversified during Evolution    

Abstract: Casein kinase II (CK2) is a protein kinase with an evolutionarily conserved function as a circadian clock component in several organisms, including the long-day plant Arabidopsis (Arabidopsis thaliana). The circadian clock component CIRCADIAN CLOCK ASSOCIATED1 (CCA1) is a CK2 target in Arabidopsis, where it influences photoperiodic flowering. In rice (Oryza sativa), a shortday plant, Heading date6 (Hd6) encodes a CK2a subunit that delays flowering time under long-day conditions. Here, we demonstrate that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 42 publications
6
106
0
Order By: Relevance
“…Genes encoding CK2 subunits show a higher degree of redundancy in plants compared with animals (Espunya et al, 2005;Ogiso et al, 2010;Mulekar et al, 2012). Here, we found that the duplication of CK2 subunits was accompanied by functional divergence, as only CK2a3/b3 was active in PT phosphorylation.…”
Section: Rice Ck2a3/b3 Functions As a Holoenzyme To Phosphorylate Pi mentioning
confidence: 71%
See 1 more Smart Citation
“…Genes encoding CK2 subunits show a higher degree of redundancy in plants compared with animals (Espunya et al, 2005;Ogiso et al, 2010;Mulekar et al, 2012). Here, we found that the duplication of CK2 subunits was accompanied by functional divergence, as only CK2a3/b3 was active in PT phosphorylation.…”
Section: Rice Ck2a3/b3 Functions As a Holoenzyme To Phosphorylate Pi mentioning
confidence: 71%
“…FW, fresh weight. CK2 in many plant species also demonstrates that this kinase is involved in diverse pathways (Plana et al, 1991;Espunya et al, 1999;Ogiso et al, 2010;Mulekar et al, 2012).…”
Section: Rice Ck2a3/b3 Functions As a Holoenzyme To Phosphorylate Pi mentioning
confidence: 99%
“…CK2, which forms a tetrameric complex including two a-subunits and two b-subunits, is a highly conserved protein kinase and could be found in various organisms, such as yeast, plants, and mammals. CK2 can phosphorylate a range of different proteins, including transcription factors, and can modulate DNA-binding ability, intracellular localization, and protein stability by interacting with partner proteins (Ogiso et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The plant circadian system consists of biochemical timing mechanisms that temporarily modulate the function of several signalling pathways to measures changes in day-length and promote suitable timing of flowering to maximize reproductive success [2,3,6,7,9,10,[13][14][15]21,24,26,28,29,31,36,38,41,42,46,48,49,[56][57][58][59][60][61][62][63][64][65][66]. The photoperiod response on flowering time varies among grasses.…”
Section: Circadian Clock and Photoperiod Responsementioning
confidence: 99%
“…To induce delayed flowering under LD conditions, Hd6 requires the presence of functional Hd1 alleles and plays a critical role in Hd1 activity. Despite this, Hd6 regulation is not mediated by changes in the circadian clock [37,65]. The rice genome contains two important genes for photoperiodic regulation: Ehd1 and Ghd7, specific to grass species such as rice, maize and sorghum but absent in the Arabidopsis genome [44].…”
Section: Circadian Clock and Photoperiod Responsementioning
confidence: 99%